Upstairs, downstairs .....

Calculus Level 5

Consider the parabola P P with the equation x 2 8 x + 4 y = 0. x^{2} - 8x + 4y = 0. A line y = b y = b , with 0 < b < 4 0 \lt b \lt 4 , is then drawn creating two regions R 1 R_{1} and R 2 R_{2} of equal area A A where

  • R 1 R_{1} is the region bounded below by the line y = b y = b and above by the curve P P , and

  • R 2 R_{2} is the region in the first quadrant bounded above by the line y = b y = b , to the left by the y y -axis and to the right by the branch of P P nearest the y y -axis.

If A = a c A = \dfrac{a}{c} , where a a and c c are positive coprime integers, then find a + b + c . a + b + c.


The answer is 14.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

The equation for the parabola can be written as y = 1 4 ( x 4 ) 2 + 4. y = -\frac{1}{4}(x - 4)^{2} + 4.

With ( k , b ) (k,b) being the coordinates of the leftmost point of intersection of P P and the line y = b y = b , we have that b = 1 4 ( k 4 ) 2 + 4. b = -\frac{1}{4}(k - 4)^{2} + 4.

Then to have the areas of regions R 1 R_{1} and R 2 R_{2} be equal, we require that

0 k ( b + 1 4 ( x 4 ) 2 + 4 ) d x = 2 k 4 ( 1 4 ( x 4 ) 2 + 4 b ) d x \displaystyle\int_{0}^{k} (b + \frac{1}{4}(x - 4)^{2} + 4) dx = 2\int_{k}^{4} (-\frac{1}{4}(x - 4)^{2} + 4 - b) dx ,

where I made use of the symmetry of P P about the line x = 4 x = 4 . Performing the integration and simplifying, we have that

( b 4 ) k + 1 12 ( k 4 ) 3 + 16 3 = 2 [ ( 4 b ) ( 4 k ) + 1 12 ( k 4 ) 3 ] , (b - 4)k + \frac{1}{12}(k - 4)^{3} + \frac{16}{3} = 2[(4 - b)(4 - k) + \frac{1}{12}(k - 4)^{3}],

which, after substituting b 4 = 1 4 ( k 4 ) 2 b - 4 = -\frac{1}{4}(k - 4)^{2} , yields

k 4 ( k 4 ) 2 + 5 12 ( k 4 ) 3 + 16 3 = 0 -\frac{k}{4}(k - 4)^{2} + \frac{5}{12}(k - 4)^{3} + \frac{16}{3} = 0

3 k ( k 4 ) 2 + 5 ( k 4 ) 3 + 64 = 0 \Longrightarrow -3k(k - 4)^{2} + 5(k - 4)^{3} + 64 = 0

k 3 18 k 2 + 96 k 128 = 0 ( k 2 ) ( k 8 ) 2 = 0. \Longrightarrow k^{3} - 18k^{2} + 96k - 128 = 0 \Longrightarrow (k - 2)(k - 8)^{2} = 0.

Now we are looking for k < 4 k \lt 4 , i.e., to the left of the vertex of P P , so we take k = 2 k = 2 , which in turn gives us b = 3 b = 3 . Plugging these values into one of the above area integrals yields the value A = 8 3 . A = \frac{8}{3}.

Thus a + b + c = 8 + 3 + 3 = 14 . a + b + c = 8 + 3 + 3 = \boxed{14}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...